Impact of different glycaemic treatment targets on pregnancy outcomes in gestational diabetes. Issue 2 (3rd September 2018) - Abell, S. K.; Boyle, J. A.; Earnest, A.; England, P.; Nankervis, A.; Ranasinha, S.; Soldatos, G.; Wallace, E. M.; Zoungas, S.; J Teede, H.
Abstract: Aim: With no current randomized trials, we explored the impact of tight compared with standard treatment targets on pregnancy outcomes in gestational diabetes mellitus (GDM). Methods: This cohort study of singleton births ≥ 28 weeks' gestation was conducted at two major Australian maternity services (2009–2013). Standardized maternal, neonatal and birth outcomes were examined using routine healthcare data and compared for women with GDM at Service One ( n = 2885) and Service Two ( n = 1887). Services applied different treatment targets: Service One (standard targets, reference group) fasting < 5.5 mmol/l, 2‐h postprandial < 7.0 mmol/l; Service Two (tight targets) fasting < 5.0 mmol/l, 2‐h postprandial < 6.7 mmol/l. Multivariable regression with propensity score adjustment was used to examine associations between targets and outcomes. Results: GDM prevalence and insulin use were 7.9% and 31% at Service One, and 5.7% and 46% at Service Two. There were no differences in primary outcomes: birthweight > 90th centile [adjusted odds ratio (OR) 1.06, 95% confidence interval (CI) 0.87–1.30] and < 10th centile (OR 0.84, 95% CI 0.70–1.01), or secondary outcomes gestational hypertension, pre‐eclampsia, shoulder dystocia or a perinatal composite. Service Two with tight targets had increased induction of labour (OR 3.63, 95% CI 3.17–4.16), elective Caesarean section (OR 1.75, 95% CI 1.37–2.23) and Apgar scores < 7 at 5 min (OR 1.54, 95% CI 1.05–2.25), decreased hypoglycaemia (OR 0.76, 95% CI 0.61–0.94]), jaundice (OR 0.47, 95% CI 0.35–0.63) and respiratory distress (OR 0.68, 95% CI 0.47–0.98). Conclusions: Tight GDM treatment targets were associated with greater insulin use and no difference in primary birthweight outcomes. The service with tight targets had higher obstetric intervention, lower rates of reported hypoglycaemia, jaundice, respiratory distress and lower Apgar scores. High‐quality interventional data are required before tight treatment targets can be implemented. What's new?: Optimal glycaemic targets for gestational diabetes mellitus (GDM) are controversial because there are no randomized trials comparing targets and pregnancy outcomes. In this large observational study of two healthcare networks, the service with tight targets had greater insulin use and obstetric interventions than the service with standard targets. Tight targets were associated with no difference in primary birthweight or maternal outcomes, with decreased hypoglycaemia, jaundice and respiratory distress, but lower Apgar scores. Whether mixed observations relate to targets or obstetric practice variation is unclear. Clinical variation in obstetric practice was significant and insulin use alone was not a good marker of neonatal risk. Interventional studies are needed to define glycaemic targets for optimizing pregnancy outcomes.